Nanomaterials In Drug Delivery: Applications and Challenges In Medicinal Chemistry - M Ronad, P.; Ankalikar, A. A.; S. Menasinakai, A.; Ravindran, Selvan; Paul, Jenish; Sunitha, G. (Journal of Neonatal Surgery, 2025)
Drug delivery systems have been developed using nanomaterials owing to the ability of the latter to enhance the therapeutic effect by sustained release, improved solubility, and targeted delivery. This work discusses the current and possible applications of nanomaterials in medicinal chemistry for drug delivery systems. Nanocarriers used in drug delivery, such as liposomes, polymeric nanoparticles, dendrimers, and micelles, were reviewed to assess the nanoparticles used in drug delivery in the current literature. The discussion was about the use of these nanomaterials in therapy, the potential dangers, the possibility of reproducing the process, and legal aspects. A qualitative research approach was used to analyze the data, and the papers were retrieved from high-impact-factor peer-reviewed journals. The research also showed that liposomes and polymeric nanoparticles are the most commonly used nanomaterials in cancer therapy and drug delivery. Highlighted topics included toxicity, especially of positively charged nanoparticles. The main problem was that the problems of scale and regulation prevented the application of those nanomaterials in clinical practice. The study also found that biodegradable nanomaterials have a scaling-up problem. Liposomes and polymeric nanoparticles are the most suitable nanomaterials for drug delivery systems. However, no large-scale production for clinical use, as well as toxicity and regulatory issues, are the limitations. Nanomaterials should be made with enhanced properties, the approaches to their production should be optimized, and the concept of personalized treatment should be advanced.